Clinical Outcomes and Safety of Secukinumab in Thai Patients with Plaque Psoriasis: A 16-Week, Multicenter, Retrospective, Real-World Study - Bensachee Pattamadilok (2022)
Background: Secukinumab, an interleukin 17A-inhibitor approved for the treatment of moderate-to-severe plaque psoriasis, has been well-studied in phase II and III trials and shown to have a sustained high-level of clinical efficacy with good safety profile and positive impact on patients' quality of life. Nevertheless, current knowledge regarding efficacy and safety of secukinumab in a real-world setting in Thai population is still limited. Objective: To evaluate real-world clinical outcomes and safety profile of secukinumab in Thai patients with moderate to severe plaque psoriasis. Materials and Methods: A multicenter retrospective medical chart review was performed in moderate to severe plaque psoriasis patients aged 18 years or older treated with secukinumab therapy using subcutaneous injections with dosage of 300 mg at weeks 0, 1, 2, 3, and 4, and every four weeks thereafter, for at least 16 weeks between September 2017 and September 2020 at four dermatologic centers in Thailand. Clinical response, psoriasis area and severity index (PASI), and percentage of body-surface area (BSA) involved were recorded at baseline and at the fourth and sixteenth weeks after the first injection. Adverse events were also documented. Results: Eighteen patients were included in the present study. Their median (interquartile range) baseline PASI score was 21.0 (15.0). Most previously received treatment with oral systemic drugs and phototherapy. Overall, their PASI and BSA scores were significantly improved from baseline to weeks 4 and 16 (both p<0.001). PASI 75, PASI 90, and PASI 100 were achieved in 81.3%, 56.3%, and 31.3% of patients, respectively at week 4, and 100%, 100%, and 72.2% at week 16, respectively. No adverse event was reported. Conclusion: The present real-world study suggested good clinical outcomes, safety, and rapidity of action of secukinumab in Thai patients with moderate to severe plaque psoriasis.